Rural Areas Between Regional Needs and Global Challenges Transformation in Rural Space - Leimgruber, Walter; Chang, Chang-yi David; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book provides an up-to-date account of the many processes shaping and transforming rural space in various parts of the world. The various case studies focus on the multi-functionality of the rural world and the driving forces behind it. The book demonstrates that rural areas are no longer simply characterized by an agricultural economy, and instead accommodate multiple complementary activities. It also touches upon two major changes that have taken place. The first is the process of rurbanization, which has led to the clear distinction between town and countryside becoming blurred: urban traits have penetrated rural areas, and rural traits have invaded towns. The second change is that rural areas are increasingly seen as multi-functional, providers not only of food and other natural resources but also locations for the generation of renewable energy (wind farms, solar farms, biogas) and regions for the preservation of biodiversity. These transformations have resulted in a new understanding and self-image of rural areas and their populations.
Part I Introduction: Rural space between marginality and centrality. Approaches to marginality issues in rural areas -- Part II People: Impact of rural restructuring on the time-space behavioural patterns in a marginal area -- Spatial differentiation of social capital: A case study of peripheral and rural microregions in Czechia -- Rural Labour Markets and Peripherization Processes in Poland -- The role of identity in community activities of marginal rural areas -- Deconstructing financial inclusion and exclusion in the development discourse: case studies of microfinance operations in rural Bangladesh -- Part III Transformation processes: Agrarian and urban transitions in Lam Dong province, Vietnam: adaptation or marginalisation for ethnic minorities? -- The influence of globalization to overcome marginality in the Uco Valley of Mendoza, Argentina -- Advances in marginality studies in southern Mendoza, Argentine -- Demographic and economic change in small towns in New Zealand and the responses to marginalization -- Part IV Primary activities: An alternative agriculture space in an indigenous community: Kalala, Taiwan -- Restructuring of Japanese forestry and the current condition for the sustainability of more advanced forestry regions -- Urban agriculture in Zambia -- Part V Towards a multifunctional rural space: The role of traditional handicrafts in the development of rural areas: the case of Ribnica, Slovenia -- Windfarms in Champagne-Ardenne Region. An assessment of the acceptability and local governance issue -- Protected areas and the integration process of mountainous areas in mainland Southeast Asia: the case of Luang Nam Tha, Lao PDR -- Part VI Conclusion: Perspectives of rural space. .
Keywords: Human geography; Human Geography